Financial Development in Latin America and the Caribbean : The Road Ahead - de la Torre, Augusto; Ize, Alain; Schmukler, Sergio L. (World Bank, 2012)
The financial systems of the Latin America and the Caribbean region (LAC) are at a crucial juncture. After a history of recurrent instability and crisis (a trademark of the region), they now seem well poised for rapid expansion. Since the last wave of financial crises that swept through the region in the late 1990s and early 2000s, financial systems in LAC have continued to gain in soundness, depth, and diversity. The size of banking systems has increased, albeit from a low base; local currency bond markets have greatly developed, both in volumes and in reach over the yield curve; stock markets have expanded; and derivative markets particularly currency derivatives have grown and multiplied. Institutional investors have become more important relative to banks, making the financial system more complex and diversified. Importantly, much progress has been made in financial inclusion, particularly through the expansion of payments, savings, and credit services to lower income households and microenterprises. As evidence of their new soundness and resiliency, financial systems in the region, except in some Caribbean countries, weathered the recent global financial crisis remarkably well. The progress in financial development in LAC no doubt reflects substantial improvements in the enabling environment, lower macroeconomic volatility, more independent and better-anchored currencies, increased financial liberalization, lower currency mismatches and foreign debt exposures, enhanced effectiveness of regulation and supervision, and notable improvements in the underlying market infrastructures (for example, trading, payments, custody, clearing, and settlement). This regional flagship report aims at providing such a stocktaking and forward looking assessment of the region's financial development. Rather than going into detail about sector-specific issues, the report focuses on the main architectural issues, overall perspectives, and interconnections. The value added of the report thus hinges on its holistic view of the development process, its broad coverage of the financial services industry (not just banking), its emphasis on benchmarking, its systemic perspective, and its explicit effort to incorporate the lessons from the recent global financial crisis.